2023
DOI: 10.1002/aenm.202203066
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Selective Interface for Kinetically Enhanced Dendrite‐Free Zn Anodes

Abstract: standard hydrogen electrode (SHE)], natural abundance, and excellent safety of Zn anode, aqueous zinc-ion batteries (AZIBs) have recently attracted considerable research attention. [1][2][3][4] Nevertheless, dendrite growth, corrosion, and passivation at the anode-electrolyte interface hinder the widespread practical application of AZIBs. [5,6] Specifically, cumulatively grown dendrites pierce the separator, resulting in poor battery performance and even fire hazards. Additionally, the accumulation of insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Despite the substantially increased viscosity, the LP9 electrolyte membrane exhibits a high ionic conductivity of 19.6 mS/cm, albeit lower than that (51.9 mS/cm) of the BE, surpassing the performance of previously reported gel electrolytes and water-in-salt electrolytes. , Moreover, as shown in Figure S10, the LP9 electrolyte membrane exhibits a Zn 2+ transference number of 0.76, higher than those of conventional liquid electrolytes. , This could be attributed to the 2D nanostructures and the highly negatively charged basal plane of the LP nanocrystals, which facilitate fast cation diffusion in the quasi-solid-state electrolyte membrane , Figure d presents the storage modulus ( G′ ) of the LP-based electrolyte membranes, and the inserted optical image shows the appearance of a freestanding LP9 electrolyte membrane. Notably, the LP6 and LP9 electrolyte membranes exhibit high G′ values of 0.8 and 2.0 MPa, respectively, signifying their exceptional mechanical resistance against Zn dendrite growth.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite the substantially increased viscosity, the LP9 electrolyte membrane exhibits a high ionic conductivity of 19.6 mS/cm, albeit lower than that (51.9 mS/cm) of the BE, surpassing the performance of previously reported gel electrolytes and water-in-salt electrolytes. , Moreover, as shown in Figure S10, the LP9 electrolyte membrane exhibits a Zn 2+ transference number of 0.76, higher than those of conventional liquid electrolytes. , This could be attributed to the 2D nanostructures and the highly negatively charged basal plane of the LP nanocrystals, which facilitate fast cation diffusion in the quasi-solid-state electrolyte membrane , Figure d presents the storage modulus ( G′ ) of the LP-based electrolyte membranes, and the inserted optical image shows the appearance of a freestanding LP9 electrolyte membrane. Notably, the LP6 and LP9 electrolyte membranes exhibit high G′ values of 0.8 and 2.0 MPa, respectively, signifying their exceptional mechanical resistance against Zn dendrite growth.…”
Section: Resultsmentioning
confidence: 74%
“…49,50 This could be attributed to the 2D nanostructures and the highly negatively charged basal plane of the LP nanocrystals, which facilitate fast cation diffusion in the quasi-solid-state electrolyte membrane. 4849,51 Figure 2d presents the storage modulus (G′) of the LP-based electrolyte membranes, and the inserted optical image shows the appearance of a freestanding LP9 electrolyte membrane. Notably, the LP6 and LP9 electrolyte membranes exhibit high G′ values of 0.8 and 2.0 MPa, respectively, signifying their exceptional mechanical resistance against Zn dendrite growth.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, the transfer process of Zn 2+ can be regulated by the PSBMA SEI layer. Due to the abundant –SO 3 – groups in the PSBMA polymer brushes, Zn 2+ can be attracted by the electrostatic attraction, which promotes the desolvation process of [Zn­(H 2 O) 6 ] 2+ and the migration of Zn 2+ . Moreover, the evenly distributed –SO 3 – can ensure a uniform flux of Zn 2+ , avoiding excessive local electric field intensity and ensuring the uniform deposition of Zn.…”
Section: Resultsmentioning
confidence: 99%
“…− groups in the PSBMA polymer brushes, Zn 2+ can be attracted by the electrostatic attraction, which promotes the desolvation process of [Zn(H 2 O) 6 ] 2+ and the migration of Zn 2+ . 29 Moreover, the evenly distributed −SO 3 − can ensure a uniform flux of Zn 2+ , avoiding excessive local electric field intensity and ensuring the uniform deposition of Zn. The sulfonic acid group can also prevent SO 4…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lower potentials indicated that the charge distribution at the Zn-CCS interface was changed and the adsorption of anions was significantly weakened in the same environment. 30,31 Besides, Zn-CCS was rich in hydrophilic functional groups and had a network-like surface with a high specific surface area, which made it have good wettability to aqueous electrolytes than bare Zn (89°) and was beneficial for the Zn ion diffusion (Figure 2i). 32 Among this, the surface morphology becomes flat from unevenness as the electrodeposition time grows with the continuous generation of Zn-CCS, and thus, the apparent contact angle continues to increase (30 s−37°, 60 s−44°, 90s-50°, 120s-52°, 150s-68°, 180s-73°).…”
Section: Resultsmentioning
confidence: 99%